Contrast Induced Nephropathy in Post PCI Patients at an Indian Tertiary Care Institute - Cinosh Mathew; Rachit Saxena; Aseem Yadav; Abhishek Gupta (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Aims: This observational investigation aimed to determine the incidence of contrast-induced nephropathy and the factors predicting its development after Percutaneous Coronary Intervention at our Institute. Materials and Methods: The study included 520 patients who underwent Percutaneous Coronary Angioplasty within a one-year period at our institution and met the inclusion criteria. Renal parameters, including serum Creatinine and Blood Urea levels, were assessed at baseline, 24 hours, and 48 hours post-procedure. Contrast-induced nephropathy was defined as a >25% increase or >0.5 mg/dl rise in pre-catheterization serum creatinine at or after 48 hours following the intervention after other causes of renal impairment had been excluded. Results: In the study, 67 patients (12.88%) developed Contrast-induced Nephropathy post-PCI which was in line with previous studies on this matter. Advanced age, diabetes mellitus, hypertension, and anaemia were identified as significant predictors of CIN. Moreover, higher contrast volume and elevated baseline creatinine levels were associated with an increased risk of CIN. Conclusions: The occurrence of CIN is a recognized complication of PCI which leads to increased mortality and morbidity and the high cost of managing such patients, which can largely be mitigated through the identification of patients with predisposing factors and the implementation of preventive measures in accordance with guideline recommendations.